Nuolaidos šalutinių sakinių modeliai Mikalojaus Daukšos raštuose - Liutkutė, Jovita (Baltistica, 2000)
Patterns of subordinate clauses of concession in Mikalojus Daukša’s writingsDaukša uses two-place conjunctions to join the subordinate clauses of concession to the main clause (69%). The first component of the conjunction is the Lithuanian hypotactic conjunction norint or the borrowings kačeib, kačeiba, kačieb. The second component of the conjunction is most often the conjunction bet/bat and (o) vienok and sometimes tačiau or o.All the other subordinate clauses in Daukša’s works are joined to the main clause by means of the conjunction norint (31%).The order of the clauses is not fixed, except sentences with two-place conjunctions.There is a clear connection between the position of the constituents of the subordinate clauses of concession and the conjunctions that are used to join them. In preposition and interposition, in the majority of cases, the two-place conjunctions are used, whereas in postposition the conjunction norint prevails.The predicates of the subordinate clauses expressing concession in Daukša’s writings coincide in their form with those in Modern Lithuanian.
Keywords: lietuvių kalba; senieji raštai; sintaksė